Association between Platelet Count and Treatment Effect of Ticagrelor or Prasugrel in Patients with Acute Coronary Syndromes - Koch, Tobias; Lahu, Shqipdona; Coughlan, J. J.; Cassese, Salvatore; Voll, Felix; Ndrepepa, Gjin; Menichelli, Maurizio; Valina, Christian; Hemetsberger, Rayyan; Witzenbichler, Bernhard; Bernlochner, Isabell; Joner, Michael; et al. (Thrombosis and Haemostasis, 2022)
Background: The relative efficacy and safety of ticagrelor and prasugrel based dual antiplatelet therapy (DAPT) strategies according to the platelet count (PC) in patients with acute coronary syndromes (ACS) has not been defined. Methods: This is a post-hoc analysis of the ISAR-REACT 5 trial, in which patients presenting with ACS were randomized to treatment with ticagrelor versus prasugrel. Patients were divided into quartiles according to PC. The primary endpoint was incidence of death, myocardial infarction, or stroke, safety endpoint was incidence of BARC type 3-5 bleeding at 12 months. Results: 3,943 patients with known PC (997 patients in quartile 1 (Q1), 1,003 in quartile 2 (Q2) 205 ± 10.3 x 109/L, 961 patients in quartile 3 (Q3) 241 ± 11.7x 109/L and 982 patients in quartile 4 (Q4) 317 ± 68.6 x 109/L). There was no significant interaction between treatment arm (ticagrelor versus prasugrel) and PC-group with respect to primary endpoint [Q1: 8.8% versus 6.3%, hazard ratio HR =1.41; 95%-CI: [0.89-2.23]; P=0.148, Q2: 9.9% versus 5.8% (HR=1.68 [1.06-2.66]; P=0.027, Q3: 7.8% versus 5.5 % (HR=1.43 [0.87-2.37]; P=0.159, Q4: 10.1% versus 10.1%, (HR=1.05 [0.71-1.57]; P=0.799; P for interaction pint=0,482] and with respect to bleeding endpoint [Q1: 5.8% versus 4.2%, (HR=1.41 [0.76-2.63]; P=0.279, Q2: 6.4% versus 3.7% (HR=1.62 [0.85-2.06]; P=0.140, Q3: 4.4% versus 3.0 % (HR=1.53 [0.73-3.18]; P=0.258, Q4: 5.6% versus 8.5%, (HR=0.67 [0.40-1.14]; P=0.138, pint=0.102]. Conclusions: In this analysis, incidence of ischemic and bleeding events at 12 months are comparable across quartiles of platelet count.
CRIS-Team Scopus Importer:2023-03-08